The visual world of Muslim India the art, culture and society of the Deccan in the early modern era - Sardar, Marika; Simpkins, Robert Alan; Sohoni, Pushkar; Michell, George; Philon, Helen; Rotzer, Klaus; Kruijtzer, Gijs; Weinstein, Laura; Hutton, Deborah; Tucker, Rebecca; Overton, Keelan; Haidar, Navina Najat; et al. (I.B. Tauris, 2014)
Selection of papers presented at a conference 'Art, Patronage and Society in the Muslim Deccan from the Fourteenth Century to the Present Day' (4-6 July 2008) at St. Antony's College, Oxford, with support from the John Fell Fund, Barakat Trust and Alessandro Bruschettini.